God’s Existence: A Maudhu’I (Thematic) Qur’anic Exegesis Integrating The Senses And The Heart In Understanding Study - Muhammad Hariyadi; Supriadi A.M; Firdaus Firdaus; Zaelani Ibrahim (ZAD Al-Mufassirin, 2026)
This study aims to analyze the concept of integrating the senses and the heart in recognizing the existence of God from the perspective of the Qur'an. This study employs a qualitative approach using library research and the thematic interpretation (tafsir maudhu'i) method. The findings reveal that the senses perceive empirical signs (ayat kauniyah) that demonstrate Allah’s power, while the interprets,  internalizes, and affirms the truth thus obtained, thereby generating faith in Allah. The integration of the two occurs through empirical observation, rational reflection, and spiritual internalization, leading to the development of God-consciousness. This study contributes by proposing an epistemological model of recognizing God that positions the senses and the heart as complementary instruments, thereby enriching thematic Qur'anic studies that have generally been discussed separately. The implications of this study indicate that recognizing God through the integration of the senses and the heart contributes to the development of reflective faith, deeper spiritual awareness, and the advancement of knowledge integrated with divine values.